ANGSTROM-PRESCOTT COEFFICIENTS AND ITS INFLUENCE ON SOLAR RADIATION AND ETO IN THE BEBEDOUROIRRIGATION PERIMETER, PETROLINA-PE - DA SILVA, A.O. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The solar radiation is an important meteorological element for the calculation of reference evapotranspiration and hence to estimate crop water consumption. The present study investigated the coefficients a and b of Angstrom-Prescott equation for the irrigated perimeter of Bebedouro in Petrolina-PE and its influence on solar radiation and evapotranspiration reference. The data (solar radiation and heat stroke) were obtained from a meteorological station (1968-2011) located at the experimental station of Embrapa Semi-Arid in Bebedouro, Petrolina-PE. The coefficients a and b were determined by linear regression analysis, for the entire period and for monthly and annual periods. Using the coefficients were estimated to solar radiation and evapotranspiration, evaluating their performance. The monthly average values of the linear coefficient (a) ranged from 0.2467 (September) to 0.3211 (January) and slope ranged (b) from 0.2785 (January) to 0.3637 (September). The best performances were obtained for the estimates in the monthly and annual scale.